2008
DOI: 10.1215/15228517-2008-027
|View full text |Cite
|
Sign up to set email alerts
|

Prediction of volumetric change in the “triple ring” caused by glioma I-125 brachytherapy

Abstract: The aim of this study was to reveal the volumetric changes in tumor necrosis, reactive zone, and edema referred to as the "triple ring" appearing after low-dose-rate iodine-125 (I-125) interstitial irradiation of 20 inoperable low-grade gliomas. To enable prediction of these volumetric changes, we provide mathematical expressions that describe the dynamics of the triple ring. Volumes of the three regions on image-fused control CT/MR images were measured for a 24-month period. The delivered dose on the tumor su… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
4
0

Year Published

2012
2012
2023
2023

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(4 citation statements)
references
References 16 publications
0
4
0
Order By: Relevance
“…A long-lasting temporary increase (up to 2 years) in capillary permeability (in the vicinity of the therapeutic intratumoral radionecrosis) accompanied by variable degrees of vasogenic edema and concomitantly reduced regional cerebral blood flow have been shown to occur [19][20][21] ; correspondingly, gadolinium-enhanced followup MRI indicates the evolution of so-called triple ring formations as early as 3 months after SBT, which usually increase slowly from the center of the implanted radioactive sources to the periphery and might exceed even the initial tumor volume during the first year after implantation. 3,22 Molecular imaging with PET using radiolabeled amino acid analogues, particularly [methyl-11 C]-Lmethionine (MET) and FET, might help overcome the limitations of morphologic imaging methods as the assessment of BTV based on MET-PET and FET-PET is considered to improve the definition of the tumor borders and tumor volume. A MET-PET study showed that in 74% of patients with high-grade glioma, pathologic amino acid uptake was found outside the abnormal contrast enhancement revealed by MRI, whereas in 100% of the patients, the hyperintensity region on T 2 -weighted MRI extended beyond the MET enhancement area.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…A long-lasting temporary increase (up to 2 years) in capillary permeability (in the vicinity of the therapeutic intratumoral radionecrosis) accompanied by variable degrees of vasogenic edema and concomitantly reduced regional cerebral blood flow have been shown to occur [19][20][21] ; correspondingly, gadolinium-enhanced followup MRI indicates the evolution of so-called triple ring formations as early as 3 months after SBT, which usually increase slowly from the center of the implanted radioactive sources to the periphery and might exceed even the initial tumor volume during the first year after implantation. 3,22 Molecular imaging with PET using radiolabeled amino acid analogues, particularly [methyl-11 C]-Lmethionine (MET) and FET, might help overcome the limitations of morphologic imaging methods as the assessment of BTV based on MET-PET and FET-PET is considered to improve the definition of the tumor borders and tumor volume. A MET-PET study showed that in 74% of patients with high-grade glioma, pathologic amino acid uptake was found outside the abnormal contrast enhancement revealed by MRI, whereas in 100% of the patients, the hyperintensity region on T 2 -weighted MRI extended beyond the MET enhancement area.…”
Section: Discussionmentioning
confidence: 99%
“…The inner zone of this so-called ''triple ring'' formation represents necrotized tumor, which is surrounded by a small rim of tissue with increased permeability; the outer zone refers to treatment-induced edema. 3 Given that treatment-induced disturbances of the blood-brain barrier can last up to 24 months after implantation and might significantly exceed the initial tumor/treatment volume, it becomes clear that any valid distinction between a tumor recurrence and benign treatment-induced imaging changes appears elusive using standard MRI protocols. [4][5][6] Molecular imaging techniques using radiolabeled amino acids have been shown to be highly useful to distinguish between the benign side effects of the therapy and tumor recurrence in multimodally treated glioma patients.…”
mentioning
confidence: 99%
“…The reactive zone has had its maximum 2 months after irradiation, after 12 months the shrinkage has been more pronounced. The maximum of the oedema has been reached after 6 months [ 86 ].…”
Section: Reviewmentioning
confidence: 99%
“…On the other hand, in post-operative verification, the newly enlarged edematous area is thought to be caused by surgical operation and implanted seeds [ 25 ], so it should not be included in the target volume. MR imaging is more accurate than CT imaging in identifying the boundary between tumor and edema [ 26 , 27 ] and MR-based fusion images are more suitable for TPS.…”
Section: Discussionmentioning
confidence: 99%